Situational Configuration Causing Riots in Correctional Institutions and Detention Centers in Indonesia - Arief, M. Sofyan; Meliala, Adrianus; Sulhin, Iqrak (International Journal Labs, 2025)
The examination of riots in Correctional Institutions and Detention Centers has so far only revealed the triggers of the riots, without exploring how riots can occur in Correctional Institutions and Detention Centers in Indonesia. This research was conducted on riots in the period 2001-2021 which had an impact on the riots, both in terms of casualties and large material impacts. Research on 8 (eight) Correctional Institutions and Detention Centers was aimed at exploring more fundamental problems in order to understand how riots can occur in Correctional Institutions and Detention Centers. Qualitative methodology was carried out in this research in order to obtain an in-depth study of the causes of the riots that occurred. The findings of this research indicate that the cause of the riots lies in the fundamental problem, namely the existence of corrupt practices in the structures that are formed formally and informally in the operationalization of Correctional Institutions and Detention Centers in Indonesia.